The Role of Peruvian Universities in Research and Technological Development - Medina Coronado, Daniela (2018)
Within the framework of the current University Law 30220 and the processes involved in its implementation in search for quality of higher education, this article is written to introduce the reader to what Peruvian universities are and should be doing to fulfill one of their important roles: research and technological development. Different documentary sources are reviewed based on the components of the research work referred to in the Frascati Manual: scientific teaching and training, research and development and technological scientific services.